2016
DOI: 10.1097/ccm.0000000000001719
|View full text |Cite
|
Sign up to set email alerts
|

A Time-Motion Study of ICU Workflow and the Impact of Strain*

Abstract: Clinicians spend the bulk of their time in the ICU on professional communication and tasks involving computers. With the strain of high severity of illness and a full unit, clinicians reallocate time from documentation to patient care and education. Further efforts are needed to examine system-related aspects of care to understand the impact of workflow and strain on patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 18 publications
0
32
0
1
Order By: Relevance
“…5 The goal of this tool is to distill the EHR into a timeline of key data, which requires a detailed understanding of relative informational value and information access patterns-which data to show, when, and how? While existing research has evaluated some aspects of EHR information use and workflow in critical care, [6][7][8][9][10][11] detailed descriptions of these concepts could not be identified, particularly for unstructured/semistructured data like clinical notes. After conducting a preliminary survey study on the topic, 12 we identified the need for direct observation of clinician-EHR behavior to overcome limitations of recall bias and analyze specific workflow sequence, prompting the present study.…”
Section: Background and Significancementioning
confidence: 99%
See 1 more Smart Citation
“…5 The goal of this tool is to distill the EHR into a timeline of key data, which requires a detailed understanding of relative informational value and information access patterns-which data to show, when, and how? While existing research has evaluated some aspects of EHR information use and workflow in critical care, [6][7][8][9][10][11] detailed descriptions of these concepts could not be identified, particularly for unstructured/semistructured data like clinical notes. After conducting a preliminary survey study on the topic, 12 we identified the need for direct observation of clinician-EHR behavior to overcome limitations of recall bias and analyze specific workflow sequence, prompting the present study.…”
Section: Background and Significancementioning
confidence: 99%
“…4/2017 their usual chart review task in their natural environment, rather than a simulation-laboratory study. Although eye tracking/screen capture methods allow precise recording of clinician-EHR interactions, 4,18,21,22 manual observational methods are a common choice in critical care settings 9,11,23,24 likely due to greater flexibility and less intrusion into native workflows, yet still providing adequate fidelity. While we acknowledge the possibility of a Hawthorne effect, the observation protocol made every attempt to minimize this influence.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Time motion studies are currently the gold standard for analyzing work patterns, and have been previously utilized in the adult ICU setting. 6 Carayon et al described that, upon implementation of EHR technology, increased time was spent performing clinical review and documentation 5 however, the amount of physical care provided to the patient was unchanged. Hefter et al performed the largest time motion study to date, and demonstrated that as the average illness severity in the unit increased, more time was spent on direct patient care and less time on computer tasks.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, existing data suggests that adult critical care physicians are spending the majority of their time using the EHR instead of being at the patient's bedside. 5,6 On the other, thorough clinical review and processing of patient data retrieved from the EHR is important, as studies have shown that data gathering for daily intensive care unit (ICU) rounds is prone to omissions and inaccuracies. 7 In addition, previous research has also shown that inadequate analysis leads to diagnostic error and patient harm.…”
Section: Background and Significancementioning
confidence: 99%
“…For example, one study demonstrated that as admissions and census increase, the odds of appropriate venous thromboembolism prophylaxis decreases, particularly among patients in closed ICUs. (9) Increasing ICU strain also influences physician workflow, with studies showing that strain is associated with increased time spent on direct patient care and trainee education, (10) reduced documentation time, (10) and decreased time spent on newly admitted patients. (11) These studies collectively demonstrate that ICU resources (including clinicians' time) are allocated differently under conditions of strain.…”
Section: What Are the Implications Of Intensive Care Unit Capacity Stmentioning
confidence: 99%